2010
DOI: 10.4149/neo_2010_04_333
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of estrogens, catecholestrogens and phytoestrogens in carriers of BRCA1 gene mutations: effects of metformin

Abstract: BRCA1 gene mutation is associated with a combination of excessive aromatase activity/expression, predominantly estrogen receptor-negative phenotypes of tumors, and only scarce information about estrogen contents in body fluids. In the present work, isotope dilution capillary gas chromatography/mass spectrometry was used to study urinary excretion of estrogens, their catechol metabolites, and phytoestrogens in 22 women (11 with BCRA1 gene mutations and 11 without these mutations) in average 5.1+/-0.4 years befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
1
7
0
1
Order By: Relevance
“…The high-risk group included women with a first-degree family history, history of lobular or ductal carcinoma in situ, fibrocystic breast disease, BRCA mutation, or Ashkenazi Jewish descent [10]. In their evaluation of estrogen metabolite excretion among breast cancer patients with and without a BRCA1 mutation, Berstein et al [37], observed significantly higher estradiol and estrone excretion in the mutation carriers; however, the 2:16a-OHE ratio was similar between the two groups. A cancer predictive role of the 2:16a-OHE ratio specifically among women with a BRCA mutation is not known.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The high-risk group included women with a first-degree family history, history of lobular or ductal carcinoma in situ, fibrocystic breast disease, BRCA mutation, or Ashkenazi Jewish descent [10]. In their evaluation of estrogen metabolite excretion among breast cancer patients with and without a BRCA1 mutation, Berstein et al [37], observed significantly higher estradiol and estrone excretion in the mutation carriers; however, the 2:16a-OHE ratio was similar between the two groups. A cancer predictive role of the 2:16a-OHE ratio specifically among women with a BRCA mutation is not known.…”
Section: Discussionmentioning
confidence: 95%
“…There is epidemiologic evidence, albeit not entirely conclusive, suggesting that a higher 2:16a-OHE ratio is associated with a reduced risk of breast cancer in both preand post-menopausal women [27,[33][34][35][36]. Results from three distinct groups evaluating a cancer-predictive role of estrogen metabolite levels among high-risk women have been inconclusive, possibly as a result of differing definitions of high-risk [10,25,37]. In the first study, Ursin et al, reported no significant difference in the 2:16a-OHE ratio between women with and without a family history of breast cancer which they defined as women with an affected first degree relative [25].…”
Section: Discussionmentioning
confidence: 97%
“…In this regard, other physiological eVects related to BRCA1-encoded gene alterations are continuously appearing. For example, diVerent excretion of estrogens and response of circulating blood cells to clastogens have been associated with BRCA1-encoded gene mutations (Berstein et al 2010;Trenz et al 2003). Moreover, Zielinski et al have demonstrated that mutations in BRCA1 gene were associated with deWciency in the production of inXammation-related agents from blood cells (Zielinski et al 2003).…”
Section: Considerations and Conclusionmentioning
confidence: 96%
“…BRCA1 appears to directly recapitulate the AMPK-related anti-lipogenic effects of metformin (which rapidly induces inhibitory phosphorylation of Acetyl-CoA Carboxylase [ACACA] -the first committed molecule in the endogenous pathway of fatty acid biosynthesis-) because specific sequences of BRCA1 have been found to interact with and stabilize the phosphorylated form of ACACA, thus interfering with ACACA lipogenic activity by preventing ACACA dephosphorylation [87,88]. Because BRCA1 selectively inhibits aromatase expression and thus local, pro-tumorigenic estrogen production in breast adipose fibroblasts, breast adipose stromal cells and breast malignant epithelial cells [89-91], metformin's ability to concurrently inhibit IGF-1, endogenous lipogenesis and aromatase expression [92-94] must be carefully evaluated on its impact against the “endocrine-genotoxic liberation” [86] that occurs upon transfer from the wild-type to the mutant BRCA1 [86,95]. Further studies are warranted to evaluate if metformin treatment significantly modifies cancer risk due to deleterious BRCA1 gene mutations to decrease middle-age women mortality and/or late-onset familial cancer.…”
Section: Metformin and Genetic Predisposition To Breast Cancermentioning
confidence: 99%